Analysis of wear properties of aluminium based journal bearing alloys with and without lubrication. - Joy Mathavan, J.; Patnaik, A. (IOP Conference Series: Materials Science and Engineering., 2016)
Apart from classical bearing materials, Aluminium alloys are used as bearing materials these days because of their superior quality. In this analysis, new Aluminium based bearing materials, with filler metals Si, Ni, and Cr are prepared by metal mould casting in burnout furnace machine, and tribological properties of these alloys with and without lubrication were tested. The experiments for wear with lubrication are conducted on multiple specimen tester and experiments without lubrication is conducted on Pin on disk tribometer. The disc material used was SAE 1050 steel. Wear tests were conducted at a sliding speed of 0.785 m/s and at a normal load of 20 N. Coefficient of friction values, temperature changes and wear of the specimens were plotted on graph according to the above mentioned working conditions. Hardness and weight losses of the specimens were calculated. The obtained results demonstrate how the friction and wear properties of these samples have changed with the % addition of Silicon, Chromium and Nickel to the base metal aluminium.